The association graph and the multigraph for loglinear models - Khamis, Harry (Thousand Oaks, Calif. ; London : SAGE, 2011)
Looking at the multigraph representations of loglinear models this is a clear, introductory text on the area of graphical models and is an ideal text for those new to the field.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Statistics -- Graphic methods; Log-linear models; Statistics. -- Graphic methods